1970
DOI: 10.4314/ejhs.v28i5.16
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Metabolic Syndrome and Its Components among Type 2 Diabetes Mellitus Patients at a Tertiary Hospital, Northwest Ethiopia

Abstract: BACKGROUND: Metabolic syndrome is a cluster of risk factors that is responsible for the risk of coronary heart disease and stroke. Therefore, the aim of this study was to assess the prevalence of MetS and its components among T2DM patients.METHODS: A cross-sectional study was conducted at the Diabetes Clinic of the Hospital, from June to July, 2015. Data were entered into EPI INFO software and exported to SPSS 20 for analysis. MetS prevalence was estimated using NCEP ATPIII and IDF criteria. Anthropometric mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
6
32
1
2
Order By: Relevance
“…The prevalence of metabolic syndrome in this study is lower compared to findings of studies done in Ghana [ 24 ] and rural Uganda [ 24 ]. Similarly, the prevalence of metabolic syndrome in the study was lower than reports in Jimma, South West Ethiopia, and that of the University of Gondar Hospital [ 19 , 28 ]; but those two studies were conducted among individuals with mental health problems. This finding is lower than the report from other studies conducted in Mekelle, Northern Ethiopia (20.8%), and Haramaya University employees (20.1%) in Eastern Ethiopia; and, it is also lower than the pooled prevalence (34.9%) done in Ethiopia [ 14 , 15 ].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of metabolic syndrome in this study is lower compared to findings of studies done in Ghana [ 24 ] and rural Uganda [ 24 ]. Similarly, the prevalence of metabolic syndrome in the study was lower than reports in Jimma, South West Ethiopia, and that of the University of Gondar Hospital [ 19 , 28 ]; but those two studies were conducted among individuals with mental health problems. This finding is lower than the report from other studies conducted in Mekelle, Northern Ethiopia (20.8%), and Haramaya University employees (20.1%) in Eastern Ethiopia; and, it is also lower than the pooled prevalence (34.9%) done in Ethiopia [ 14 , 15 ].…”
Section: Discussioncontrasting
confidence: 49%
“…Hence, this study assessed metabolic syndrome using both criteria (ATP III and IDF) and found criteria agreements for the same study population at the community level which will show a better picture of the distribution of metabolic syndrome with different factors [ 1 ]. Moreover, previous studies seem to have gaps in terms of lifestyle and anthropological perspectives which are needed to explain the reasons, deterrence, and control of metabolic syndrome, especially in Ethiopia, where health outcomes are highly dependent on dietary practice [ 18 , 19 ]. Therefore, establishing community-based baseline data on the prevalence of metabolic syndrome using Adult Treatment Panel III (ATP III and IDF) is imperative to developing and strengthening national NCD prevention and control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Its predominant vasoconstriction effect is appeared through the activation of its endothelin A (ETA) and Endothelin B (ETB) receptors through the body organs and vessels [2]. Usually, T2DM is accompanied by hypertriglyceridemia [3], hypercholesterolemia [4], hyperuricemia [5], and hyperhomocysteinemia [6] and hypertension. These effects change the tone and stability of vasculatures, causing a mechanical stress on veins and arteries that are already under oxidative stress load in T2DM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these disorders is a well-known risk factor for cardiovascular disease and type 2 diabetes (5). The prevalence of MetS has been estimated at around 20-25% of the world's adult population (6). It has increased rapidly in both developed and developing countries during recent years (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%